2011
DOI: 10.1089/gtmb.2011.0028
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Genetic Testing for Alzheimer's Disease: A Measure of Personal Utility

Abstract: Background: The increased availability of genetic tests for common, complex diseases, such as Alzheimer's disease (AD), raises questions about what people are willing to pay for these services. Methods: We studied willingness-to-pay for genetic testing in a study of AD risk assessment that included APOE genotype disclosure among 276 first-degree relatives of persons with AD. Results: Seventy-one percent reported that they would ask for such testing from their doctor if it were covered by health insurance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 15 publications
1
47
0
3
Order By: Relevance
“…Still, a ‘negative’ test result may offer relief and reduce uncertainty and anxiety, whereas consumers with a highly increased risk may undertake psychological and practical preparations for a possible future. Research participants have reported that genomic testing for Alzheimer's disease may be a coping strategy,10 and a source of valuable information for making important life decisions,11 for tested individuals themselves as well as for their family members. It is a matter of debate whether such psychological and personal options fit within the goals of medicine.…”
Section: Two Perspectives On the Notion Of Personal Utilitymentioning
confidence: 99%
“…Still, a ‘negative’ test result may offer relief and reduce uncertainty and anxiety, whereas consumers with a highly increased risk may undertake psychological and practical preparations for a possible future. Research participants have reported that genomic testing for Alzheimer's disease may be a coping strategy,10 and a source of valuable information for making important life decisions,11 for tested individuals themselves as well as for their family members. It is a matter of debate whether such psychological and personal options fit within the goals of medicine.…”
Section: Two Perspectives On the Notion Of Personal Utilitymentioning
confidence: 99%
“…21 Furthermore, clinical utility has a subjective dimension in that, for example, the consumer may find a result useful whereas a physician may not. 22,23 In the view of EASAC-FEAM, it is essential that whatever information exists on the validity and usefulness of a test it is placed in the public domain so that physician and consumer can judge whether or not to avail of a particular service. There is a concomitant need to educate the public to understand what is offered in DTC services, for example to explain the distinction made between testing for monogenic and complex disorders.…”
Section: Governance Principles For Informing Policy Developmentmentioning
confidence: 99%
“…In fact, APOE testing for AD risk is often mentioned as a paradigmatic example of the personal utility of predictive tests19 20: knowledge of one’s AD risk is thought to be useful personally, rather than clinically, and is thought to affect people’s personal lives, and their social, practical, financial and lifestyle decisions. People have been found to value ‘the information itself, rather than its potential to improve their health.’23 Similar results have been found in relation to non-genetic biomarker testing, particularly among individuals who see themselves as at higher risk of AD, who have a family history of disease or who have cognitive complaints 10 25…”
Section: Defining Personal Utilitymentioning
confidence: 53%
“…Studies have shown, for instance, that people are interested in APOE susceptibility testing for AD for a variety of medical and non-medical reasons, ranging from arranging one’s financial affairs or advance care planning to preparing one’s family members for the possibility of AD or making altruistic contributions to scientific research 23. In fact, APOE testing for AD risk is often mentioned as a paradigmatic example of the personal utility of predictive tests19 20: knowledge of one’s AD risk is thought to be useful personally, rather than clinically, and is thought to affect people’s personal lives, and their social, practical, financial and lifestyle decisions.…”
Section: Defining Personal Utilitymentioning
confidence: 99%